2022
DOI: 10.3389/fnut.2022.959703
|View full text |Cite
|
Sign up to set email alerts
|

Compound dietary fiber and high-grade protein diet improves glycemic control and ameliorates diabetes and its comorbidities through remodeling the gut microbiota in mice

Abstract: Dietary intervention with a low glycemic index and full nutritional support is emerging as an effective strategy for diabetes management. Here, we found that the treatment of a novel compound dietary fiber and high-grade protein diet (CFP) improved glycemic control and insulin resistance in streptozotocin-induced diabetic mice, with a similar effect to liraglutide. In addition, CFP treatment ameliorated diabetes-related metabolic syndromes, such as hyperlipidemia, hepatic lipid accumulation and adipogenesis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Our previous clinical study results suggested that 2‐g Tempeh daily for a period of 3 months attenuated HbA1c and triglyceride levels in participants (Su et al, 2021 ). One animal study suggested that a high‐grade protein and fiber diet could remodel the gut microbiota, resulting in improved glycemic control and ameliorated diabetes (Ni et al, 2022 ). In addition, isoflavone content, polyphenol content, and antioxidant activity were increased during the fermentation of Tempeh (Kuligowski et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous clinical study results suggested that 2‐g Tempeh daily for a period of 3 months attenuated HbA1c and triglyceride levels in participants (Su et al, 2021 ). One animal study suggested that a high‐grade protein and fiber diet could remodel the gut microbiota, resulting in improved glycemic control and ameliorated diabetes (Ni et al, 2022 ). In addition, isoflavone content, polyphenol content, and antioxidant activity were increased during the fermentation of Tempeh (Kuligowski et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The administration of LKM512 exerts an anti-inflammatory effect, as well as reshaping the composition of the intestinal microbiota of the elderly 22,23) . In our previous study, we found that the supplementation of LKM512 attenuated obesityassociated inflammation and insulin resistance by modifying microbiota in high-fat diet-induced obese mice 24) . However, the potential effects of this probiotic on IBD remain unknown.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 95%
“…13,30,31 The high fiber diets potentially reduced the blood glucose levels through remodeling the gut microbes in the current study, and might act on glucose and lipid metabolism. [32][33][34] Therefore, in this study, high dietary fiber contents improved the glucose response in the healthy mouse models, although the body weight and feed intake of mice was not significantly altered. However, the limitation was that we did not detect changes to the insulin levels therefore we cannot directly declare that the insulin activity was changed by high fiber diets in this study.…”
Section: Food and Function Papermentioning
confidence: 95%
“…4 However, reduced plasma TG, TC, and NEFA levels were seen in mice with diabetes and hyperlipidemia after 12 weeks of compound dietary fiber and high protein treatment. 32 Several studies have reported improvements in the serum lipid profile including TG, TC, and LDL-C levels when the dietary carbohydrate content is replaced with protein in individuals with metabolic syndrome. 25,35 There were limited studies investigating the effects of high protein diets on healthy subjects.…”
Section: Food and Function Papermentioning
confidence: 99%